An erbium-doped yttrium aluminum garnet transparent ceramic and a preparation method and application thereof
Patent Information
- Application Number
- CN202611276798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-16
AI Technical Summary
[0006](1)均匀高浓度Er³+掺杂(如20at%)虽然可以获得较强的532nm吸收,但高浓度掺杂容易引起浓度淬灭效应和晶格畸变,导致陶瓷光学质量下降,同时在低光强下的线性透过率过低,影响正常使用;
(1)本发明通过梯度掺杂结构设计,在入射面采用较低的Er3+掺杂浓度以保证低光强下的合理线性透过率,沿光轴方向逐渐提高Er3+掺杂浓度以增强非线性吸收效率。这种"浓度梯度放大器"结构充分利用了Er3+的激发态吸收效应:入射激光在低浓度区域被部分吸收并产生激发态Er3+离子,这些激发态离子在后续高浓度区域进一步参与ESA过程,从而在整体上实现了增强的非线性光学限幅效果,同时避免了均匀高浓度掺杂导致的浓度淬灭和透过率过低问题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of transparent ceramic materials technology, and in particular to an erbium-doped yttrium aluminum garnet transparent ceramic, its preparation method, and its application. Background Technology
[0002] With the widespread application of laser technology in industrial processing, military operations, medical surgery, and scientific research, the output power of high-power 532nm green lasers is constantly increasing, posing a severe challenge to the safety protection of human eyes, optical sensors, and precision optoelectronic devices. Traditional laser protection methods, such as absorption filters and reflective dielectric films, have inherent defects such as narrow protection bandwidth, low damage threshold, and high angle dependence, making it difficult to meet the needs of next-generation high-power laser protection.
[0003] Optical limiting materials based on nonlinear optics principles can maintain high linear transmittance at low light intensities, while "clamping" the transmitted light intensity through nonlinear absorption effects when strong lasers are incident, thus protecting subsequent optoelectronic devices or human eyes. This "intelligent" protection mechanism overcomes the contradiction of traditional linear absorption protective materials having insufficient transmittance at high light intensities and excessive attenuation at low light intensities, and is currently a research hotspot in the field of laser protection.
[0004] Yttrium aluminum garnet (Y3Al5O) 12 YAG (or Y-A) possesses an isotropic cubic crystal structure, excellent thermomechanical properties, good chemical stability, and a wide transmittance range (0.2~5.5 μm), making it an ideal matrix material for preparing transparent ceramics. + Ions, due to their unique 4f electronic level structure, 4 I 15 / 2→ 4 The absorption peak corresponding to the S3 / 2 transition is located near 540 nm, which is highly matched with the 532 nm laser wavelength. Meanwhile, Er³ + Ions with high concentrations of doping can generate an effective excited-state absorption effect, thus exhibiting significant nonlinear absorption enhancement behavior under strong light.
[0005] However, the preparation of Er:YAG transparent ceramics in the existing technology still faces the following key problems that urgently need to be solved:
[0006] (1) Uniform high concentration of Er³ + While doping (e.g., 20 at%) can achieve strong absorption at 532 nm, high concentrations of doping can easily cause concentration quenching and lattice distortion, leading to a decrease in the optical quality of ceramics. At the same time, the linear transmittance at low light intensity is too low, affecting normal use. (2) Transparent ceramics prepared by solid-state reaction sintering often have defects such as residual pores and grain boundary second phase, which limit their optical quality and laser damage threshold. (3) Existing technologies lack systematic characterization and optimization of the nonlinear optical limiting performance of Er:YAG transparent ceramics. Summary of the Invention
[0007] The purpose of this invention is to provide an erbium-doped yttrium aluminum garnet transparent ceramic, its preparation method and application. It has excellent nonlinear optical limiting characteristics, high laser damage threshold and good thermomechanical properties in the 532nm band. It can be widely used in the protection of observation windows of high-power green laser processing equipment, detector protection of laser ranging / guidance systems, and protection of laser blinding weapons in the military field. It has important practical value and broad market prospects.
[0008] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A transparent erbium-doped yttrium aluminum garnet ceramic, wherein the transparent ceramic has a gradient-varying Er along the optical axis. 3+ Doping concentration distribution, Er 3+ The doping concentration increases continuously or stepwise from the incident surface to the exit surface in the range of 5 at% to 30 at%, and the chemical composition of the transparent ceramic is (Y 1-x Er x )3Al5O 12 Where x = 0.15~0.25, and x varies gradually from x1 to x2 along the thickness direction, and 0.05 ≤ x1 <x2≤0.30。
[0009] Preferably, the transparent ceramic consists of at least three layers with different Er values along its thickness direction. 3+ Sublayers with varying doping concentrations are stacked sequentially, with Er between adjacent sublayers. 3+ The doping concentration difference Δx is 2at%~10at%, the thickness of each sublayer is 0.5~5mm, and the total thickness is 2~15mm.
[0010] Preferably, the transparent ceramic is also doped with Yb. 3+ As a sensitizing ion, the Yb 3+ The doping concentration is 1 at% to 8 at%.
[0011] Preferably, the transparent ceramic has a grain size of 5~30μm, a relative density of ≥99.95%, a linear transmittance of ≥80% at a wavelength of 1064nm, a linear transmittance of 15%~40% at a low light intensity of 532nm, and a nonlinear transmittance of ≤5% at a high light intensity of 532nm.
[0012] A method for preparing erbium-doped yttrium aluminum garnet transparent ceramic includes the following steps: S1, using magnesium nitrate and tetraethyl orthosilicate as precursors, MgO-SiO2 nanocomposite powder was prepared by sol-gel method, and core-shell structured nanocomposite sintering aid with a particle size of 20-80 nm was obtained by calcination at 600-800℃ for 2-4 h. S2, calcining Y2O3, α-Al2O3, Er2O3 and Yb2O3 powders at 800~1000℃ for 4~8h respectively; S3, weigh the raw material powder according to the target stoichiometric ratio of each sublayer, add core-shell structured nanocomposite sintering aid, PEG-400 dispersant and PVB binder, use anhydrous ethanol as medium and high-purity Al2O3 balls as grinding media, ball mill for 12~20h to obtain slurries of various concentration gradients. S4. After drying, grinding and sieving the slurries of each gradient, they are laid in the mold in sequence according to the designed concentration gradient. After each layer is pre-pressed, the whole is dry-pressed and then subjected to cold isostatic pressing treatment. The pressure is 200~300MPa and the holding time is 3~10min to obtain the laminated green body. S5, the green blank is subjected to air preheating, vacuum densification, high-temperature sintering and oxygen atmosphere annealing in sequence; S6, then perform hot isostatic pressing post-treatment, with a heating rate of 10~15℃ / min, and heat to 1650~1750℃ and hold for 2~4h under argon atmosphere and 150~200MPa pressure; S7, double-sided grinding and polishing to the target thickness and surface roughness.
[0013] Preferably, the molar ratio of MgO to SiO2 in step S1 is 1:1 to 3:1.
[0014] Preferably, in step S3, the amount of core-shell structured nanocomposite sintering aid added is 0.08~0.15wt%, the amount of PEG-400 dispersant added is 0.3~0.6wt%, the amount of PVB binder added is 0.2~0.5wt%, the solid content of anhydrous ethanol in the ball milling medium is controlled at 40~50wt%, the ball-to-material mass ratio is 2:1~4:1, and the ball milling speed is 150~250r / min.
[0015] Preferably, in step S5, the air preheating temperature is 800~1000℃, the duration is 4~8h, the vacuum densification temperature is 1300~1450℃, the duration is 2~4h, and the pressure is ≤5×10 -4 Pa, high-temperature sintering temperature is 1700~1800℃, duration is 6~12h, oxygen atmosphere annealing temperature is 1400~1500℃, duration is 8~16h, oxygen partial pressure is 0.1~1atm.
[0016] Preferably, the heating rate of the vacuum densification stage is 2~5℃ / min, the heating rate of the high-temperature sintering stage is 1~3℃ / min, and the oxygen purity used in the oxygen atmosphere annealing stage is ≥99.999%.
[0017] Application of erbium-doped yttrium aluminum garnet transparent ceramic in 532nm high-power laser protection device, the laser protection device including laser protection lens, optical sensor protection window, laser processing equipment observation window and military optoelectronic countermeasures protection screen.
[0018] In summary, the present invention has the following beneficial effects: (1) This invention uses a gradient doping structure design to employ a lower Er at the incident surface. 3+ To ensure reasonable linear transmittance under low light intensity, the doping concentration is gradually increased along the optical axis by adjusting Er. 3+ The doping concentration is adjusted to enhance nonlinear absorption efficiency. This "concentration gradient amplifier" structure fully utilizes Er... 3+ Excited-state absorption effect: The incident laser is partially absorbed in the low-concentration region, generating an excited state Er. 3+ These excited-state ions further participate in the ESA process in subsequent high-concentration regions, thereby achieving an enhanced nonlinear optical limiting effect overall, while avoiding the problems of concentration quenching and low transmittance caused by uniform high-concentration doping.
[0019] (2) This invention introduces Yb 3+ As a sensitizing ion, using Yb 3+ The strong absorption band of (²F5 / 2→²F7 / 2) near 980nm and Yb 3+ →Er 3+ The efficient energy transfer (ET) mechanism can significantly enhance Er 3+4 I 11 The population efficiency of the / 2 energy level is improved, thereby promoting the excited-state absorption process and increasing the nonlinear absorption coefficient. Meanwhile, Yb³ + The introduction of [something] can also effectively suppress Er [something]. 3+ The concentration quenching effect improves the optical uniformity of ceramics.
[0020] (3) The present invention uses a self-developed MgO-SiO2 core-shell structure nanocomposite sintering aid. Compared with the traditional method of adding MgO and TEOS alone, it has the following advantages: the core-shell structure can realize the uniform dispersion and segmented release of the sintering aid. The MgO core inhibits abnormal grain growth at low temperature, and the SiO2 shell forms a trace liquid phase at high temperature to promote densification. The synergistic effect of the two can effectively reduce the sintering temperature by 50~100℃, while reducing the residual second phase at the grain boundary and improving the optical quality of ceramics.
[0021] (4) The present invention adopts a multi-step atmosphere-controlled sintering process. Through the four-stage sintering strategy of "air pre-firing → vacuum densification → high-temperature sintering → oxygen atmosphere annealing", the organic matter is fully removed, the pores are eliminated step by step and the oxygen vacancies are effectively filled. The prepared transparent ceramic has a relative density of ≥99.95% and no visible residual pores in the crystal and at the grain boundaries.
[0022] (5) The gradient-doped Er:YAG transparent ceramic prepared by the present invention exhibits excellent nonlinear optical limiting characteristics at 532nm: the transmittance is 15%~40% under low light intensity (<1kW / cm²), the nonlinear transmittance is ≤5% under high light intensity (>100MW / cm²), the nonlinear absorption coefficient β can reach 10~50cm / GW, and the laser damage threshold is ≥15J / cm² (10ns pulse). The overall performance is significantly better than the existing uniform doping scheme. Detailed Implementation
[0023] The specific embodiments of the present invention will be further described below. These embodiments do not constitute a limitation on the present invention.
[0024] Example 1: Five-layer gradient-doped 20at%Er:1at%Yb:YAG transparent ceramic This embodiment prepares a five-layer gradient-doped Er:YAG transparent ceramic, with each layer containing Er³⁺. + The doping concentrations along the optical axis are 5 at%, 10 at%, 15 at%, 20 at%, and 25 at%, respectively, for Yb³. + The material is uniformly doped in each layer with a doping concentration of 1 at%, and each layer has a thickness of 1 mm, for a total thickness of 5 mm.
[0025] S1, Preparation of nanocomposite sintering aids 12.82 g of Mg(NO3)2·6H2O was weighed and dissolved in 100 mL of anhydrous ethanol. The solution was magnetically stirred at 40 °C for 30 min until completely dissolved. 4.45 mL of tetraethyl orthosilicate (TEOS) was slowly added dropwise, and stirring was continued for 1 h. A mixture of 2 mL of deionized water and 1 mL of concentrated ammonia was added dropwise to adjust the pH to 9-10. The solution was stirred at 60 °C until a gel was formed. The gel was dried at 120 °C for 12 h, ground, and then calcined in a muffle furnace at 700 °C for 3 h to obtain MgO-SiO2 core-shell structured nanocomposite powder (MgO:SiO2 molar ratio = 2:1). TEM characterization showed that the powder particle size was 30-60 nm.
[0026] S2, Raw material pretreatment and gradient slurry preparation Y₂O₃ powder, α-Al₂O₃ powder, Er₂O₃ powder, and Yb₂O₃ powder were placed in high-purity Al₂O₃ crucibles and calcined at 900℃ for 6 hours in a muffle furnace. The raw material powders for each sublayer were weighed according to the formulas shown in Table 1.
[0027] Table 1. Raw material ratios for each sublayer in Example 1
[0028] Each sublayer powder was added separately to a nylon ball mill jar, along with 240g of high-purity Al2O3 grinding balls (5mm and 10mm in diameter mixed at a 1:1 mass ratio) and 70mL of anhydrous ethanol as the milling medium. The mixture was then milled for 16 hours at 200r / min in a planetary ball mill to obtain 5 groups of different Er³... + A uniform slurry of uniform concentration.
[0029] S3, Lamination Five groups of slurries were dried at 50℃ for 30 hours, and the dried powders were ground twice through a 200-mesh sieve. Oleic acid was evenly applied to the inner wall of a Φ30mm steel mold as a release agent. Each layer of powder was laid flat in the mold cavity in the order L1→L2→L3→L4→L5. After each layer was laid, a flat press head was used to lightly press and pre-shape it at 8MPa for 30 seconds. After all the powder was laid, it was dry-pressed at 20MPa for 5 minutes. After demolding, it was placed in a cold isostatic press and held at 250MPa for 5 minutes to obtain a laminated preform.
[0030] S4, multi-step atmosphere-controlled sintering The laminated green blanks are placed in a high-temperature sintering furnace and sintered according to the following procedure: (a) Air preheating stage: air atmosphere, temperature rises from room temperature to 900℃ at 2℃ / min, and holds for 6h; (b) Vacuum densification stage: Evacuate to 3×10 -4 Pa, heated to 1400℃ at 3℃ / min, and held at that temperature for 3h; (c) High-temperature sintering stage: Maintain vacuum, increase temperature to 1750℃ at 2℃ / min, and hold for 10h; (d) Oxygen atmosphere annealing stage: High-purity oxygen (99.999%) is introduced, oxygen partial pressure is 0.5 atm, and the temperature is reduced to 1450℃ at 5℃ / min. The temperature is held for 12h and then cooled with the furnace.
[0031] S5, post-hot isostatic pressing treatment The pre-sintered body was placed in a hot isostatic pressing furnace and heated to 1700℃ at 12℃ / min under an argon atmosphere and a pressure of 180MPa. The temperature was held for 3 hours and then cooled to room temperature without depressurization.
[0032] S6, Precision Machining The sintered ceramic block was subjected to double-sided grinding and chemical mechanical polishing (CMP) to obtain a transparent ceramic sheet with a diameter of 25mm × 5mm and a surface roughness of Ra = 0.35nm.
[0033] Example 2: Three-layer gradient-doped 15at%Er:3at%Yb:YAG transparent ceramic In this embodiment, a three-layer gradient-doped Er:YAG transparent ceramic is prepared, with each layer containing Er³. + The doping concentrations are 5 at%, 15 at%, and 25 at%, respectively, for Yb³. + The uniform doping concentration was 3 at%, with layer thicknesses of 2 mm, 2 mm, and 2 mm, for a total thickness of 6 mm. The amounts of Y₂O₃, Al₂O₃, Er₂O₃, and Yb₂O₃ were calculated based on the target stoichiometry of each layer. The addition amounts of MgO-SiO₂ nanocomposite sintering aids were 0.12 wt%, PEG-400 was 0.5 wt%, and PVB was 0.3 wt%.
[0034] (a) Air preheating stage: Heat to 850℃ at 1.5℃ / min and hold for 8 hours; (b) Vacuum densification stage: vacuum degree 4×10 -4 Pa, heated to 1380℃ at 2.5℃ / min, and held at that temperature for 4 hours; (c) High-temperature sintering stage: Maintain vacuum, raise the temperature to 1780℃ at 1.5℃ / min, and hold for 8 hours; (d) Oxygen atmosphere annealing stage: oxygen partial pressure 0.8 atm, annealing at 1450℃ for 10h.
[0035] Hot isostatic pressing conditions: argon pressure 200 MPa, temperature increased to 1750 °C at 10 °C / min, and held for 2 hours. The remaining preparation steps are the same as in Example 1.
[0036] Example 3: Seven-layer gradient-doped 25at%Er:5at%Yb:YAG transparent ceramic This embodiment prepares a seven-layer precisely gradient-doped Er:YAG transparent ceramic, with each layer containing Er³. + The doping concentrations are 5at%, 8at%, 12at%, 16at%, 20at%, 24at%, and 28at, respectively, with a doping concentration difference of 3-4at between adjacent layers, Yb³ + The uniform doping concentration is 5 at%, the thickness of each layer is 0.8 mm, the total thickness is 5.6 mm, the amount of MgO-SiO2 nanocomposite sintering aid added is 0.10 wt%, PEG-400 is 0.4 wt%, and PVB is 0.25 wt%.
[0037] (a) Air preheating stage: Heat to 1000℃ at 3℃ / min and hold for 4 hours; (b) Vacuum densification stage: vacuum degree 2×10 -4 Pa, heated to 1450℃ at 4℃ / min, and held at that temperature for 2 hours; (c) High-temperature sintering stage: Maintain vacuum, raise the temperature to 1720℃ at 2.5℃ / min, and hold for 12h; (d) Oxygen atmosphere annealing stage: oxygen partial pressure 1.0 atm, annealing at 1500℃ for 8h.
[0038] Hot isostatic pressing conditions: argon pressure 160 MPa, temperature increased to 1680 °C at 15 °C / min, and held for 4 hours. The remaining preparation steps are the same as in Example 1.
[0039] Example 4: Five-layer Er / Yb gradient co-doped YAG transparent ceramic This embodiment prepares Er³ + and Yb³ + Five-layer transparent YAG ceramic with common gradient doping. Er³ + The doping concentrations along the optical axis are 5 at%, 10 at%, 15 at%, 20 at%, and 25 at%, respectively, for Yb³. + The doping concentrations correspond to 1at%, 2at%, 4at%, 6at%, and 8at%, i.e., Yb³ + Concentration and Er³ + The concentration increased in a positive correlation. Each layer was 1.2 mm thick, with a total thickness of 6 mm. The remaining preparation steps were the same as in Example 1.
[0040] Example 5: Continuously Gradient Doped Er:YAG Transparent Ceramic This embodiment uses a continuous gradient casting method instead of layered molding. The five different Er³ samples prepared in step 3 of Example 1 are used... + A slurry of varying concentrations (Er: 5 at%~25 at%) was simultaneously injected into the molding die using a multi-channel precision injection pump. The flow rate of each channel was controlled to exhibit a linear gradient (the Er concentration was lowest on the incident side and highest on the exit side). During injection, micro-vibration promoted diffusion and mutual dissolution between the different concentration layers, forming an approximately continuous doping concentration gradient. After injection, the sample was slowly dried at 50°C for 48 hours, and then demolded to obtain a continuous gradient preform. The remaining preparation steps were the same as in Example 1.
[0041] Comparative Example 1: Uniform 20 at% Er-doped YAG transparent ceramic Prepare a uniform 20at%Er³ according to existing technology + Doped Er:YAG transparent ceramic (chemical formula (Y0.8Er0.2)3Al5O) 12The conventional sintering aid system was used: MgO 0.1wt%, TEOS (directly added, not nanocomposite) 0.8wt%, PEG200 0.5wt%, and PVB 0.3wt%. It was molded into a single-layer structure with a total thickness of 5mm. The sintering process was as follows: air pre-firing at 1000℃ / 8h → vacuum pre-firing at 1650℃ / 6h → hot isostatic pressing at 1700℃ / 200MPa / 3h → air annealing at 1450℃ / 10h. The remaining raw materials and basic steps were the same as in Example 1.
[0042] Comparative Example 2: Uniform 20 at% Er-doped YAG transparent ceramic (using the sintering aid of this invention) Using the MgO-SiO2 nanocomposite sintering aid (0.10wt%) and multi-step atmosphere-controlled sintering process of this invention, but Er³ + Uniform 20at% doping (monolayer structure), without introducing Yb³ + Sensitized ions. The remaining preparation conditions are the same as in Example 1.
[0043] Comparative Example 3: Gradient-doped Er:YAG transparent ceramic (using conventional sintering aids) The five-layer gradient doped structure of Example 1 and Yb³ were used. + The sensitization scheme was used, but a traditional sintering aid system (MgO 0.1wt% + TEOS 0.8wt% added separately) and a traditional sintering process (vacuum pre-firing 1650℃ / 6h → hot isostatic pressing 1700℃ / 3h) were employed, without using multi-step atmosphere-controlled sintering. The remaining preparation conditions were the same as in Example 1.
[0044] VI. Performance Testing and Characterization Methods X-ray diffraction (XRD) analysis Phase analysis of ceramic samples was performed using a Rigaku SmartLab X-ray diffractometer. Test conditions: Cu Kα radiation (λ = 0.15406 nm), tube voltage 40 kV, tube current 40 mA, scan step size 0.02°, scan range 2θ = 10°–90°, scan speed 4° / min. Phase identification and lattice constant calculation were performed using JADE software based on the diffraction patterns.
[0045] Microstructure characterization The microstructure of the ceramic cross-section was observed using a FEI Quanta FEG 250 field emission scanning electron microscope (SEM). Samples were subjected to thermal etching (1450℃ / 2h, air atmosphere) followed by gold sputtering for observation. Grain size was statistically analyzed using the linear intercept method, with at least 200 grains counted for each sample.
[0046] Density and relative density test The bulk density of ceramic samples was measured using the Archimedes displacement method with deionized water as the impregnation medium. Each sample was measured five times, and the average value was taken. Relative density = measured density / theoretical density × 100%, where theoretical density was calculated as a weighted average based on the chemical composition of each layer.
[0047] Linear transmittance test The linear transmittance of ceramic samples in the 300–1200 nm wavelength range was measured using a PerkinElmer Lambda 1050+ UV-Vis-NIR spectrophotometer with a scan step of 1 nm. The samples were optically polished on both sides, and the test spot diameter was 5 mm.
[0048] Nonlinear optical limiting performance testing (Z-scan method) The nonlinear optical limiting performance of the samples was tested using an open-aperture Z-scan technique. The light source was a Q-switched Nd:YAG frequency-doubled laser (wavelength 532 nm, pulse width 8 ns, repetition rate 10 Hz). The laser beam was focused by a lens with a focal length of f = 150 mm, and the sample was moved near the focal point along the optical axis (z-axis). The transmitted energy was recorded as a function of sample position at the far field using an energy meter. The nonlinear absorption coefficient β was obtained by fitting the Z-scan curve. The optical limiting threshold was defined as the incident light intensity at which the transmittance drops to 50% of the linear transmittance.
[0049] Laser Damage Threshold (LIDT) Test The laser damage threshold of samples was tested using the R-on-1 method according to ISO 21254-1:2011 standard. The light source was a Nd:YAG Q-switched laser (wavelength 532 nm, pulse width 10 ns, spot diameter (1 / e²) 0.5 mm). Ten different locations were irradiated at each energy density level, and the damage probability was statistically analyzed. The highest energy density with a damage probability of 0% was used as the zero-probability damage threshold. Damage determination criteria: irreversible surface morphology changes or a permanent decrease in transmittance ≥5% observed under an online microscope.
[0050] Thermal conductivity test The thermal diffusivity α of the ceramic samples was measured using a Netzsch LFA 467 laser flare analyzer, with a test temperature range of 25–300 °C. Specific heat capacity Cp was measured using the DSC method (Netzsch DSC 404F3). Thermal conductivity κ was calculated using the formula κ = α × ρ × Cp, where ρ is the sample density.
[0051] Test Results and Analysis Phase and microstructure The XRD patterns of the gradient-doped Er:YAG transparent ceramics prepared in Examples 1-5 all exhibit typical Y3Al5O4 characteristics. 12The cubic phase diffraction peaks of garnet (JCPDS No. 33-0040) show no diffraction peaks for the second phases such as Er₂O₃, Yb₂O₃, and Al₂O₃, indicating that Er³⁺… + and Yb³ + Completely dissolved in the YAG lattice. Compared to the standard YAG spectrum, the diffraction peaks of the example sample are slightly shifted to lower angles, consistent with the larger ionic radius Er³. + (r=1.004Å) and Yb³ + (r=0.985Å) Replace Y³ + The expected value is (r=1.019Å).
[0052] SEM observation results show that the cross-sectional microstructure of the sample in Example 1 is dense and uniform, with a grain size of 8-18 μm and an average grain size of 12.5 μm. The grain boundaries are clear and clean, and no residual pores or second phases were observed within the grains or at the grain boundaries. The interfaces between the sublayers are tightly bonded, without obvious delamination or cracking. The width of the interface transition zone is approximately 10-20 μm, and no discontinuity is observed under SEM.
[0053] Density and optical quality The density and optical quality parameters of each embodiment and comparative example are shown in Table 2 below: Table 2. Density and optical performance parameters of each embodiment and comparative example.
[0054] As shown in Table 2, (1) the gradient doping scheme of the present invention significantly improves the linear transmittance at low light intensity while maintaining effective 532nm absorption. The 532nm low light intensity transmittance of Examples 1 to 5 is 26.3% to 33.4%, which is much higher than 1.71% of Comparative Example 1 (uniform 20 at% doping) and 2.25% of Comparative Example 2. The higher transmittance at low light intensity means that the ceramic material will not excessively attenuate the normal light signal in actual use, thus improving the availability of the device. (2) The MgO-SiO2 nanocomposite sintering aid and multi-step atmosphere-controlled sintering process of the present invention effectively improve the density of the ceramic. The relative density of the examples is ≥99.95%, while the relative density of Comparative Example 3 (using traditional sintering aid) is only 99.35%.
[0055] Nonlinear optical limiting performance The nonlinear optical limiting performance parameters of each embodiment and comparative example at a wavelength of 532 nm are shown in Table 3 below: Table 3. 532nm Nonlinear Optical Constriction Performance Parameters
[0056] As can be seen from the data in Table 3: (1) Nonlinear absorption coefficient β: The nonlinear absorption coefficient β of Examples 1-5 was 22.8-36.5 cm / GW, significantly better than Comparative Example 1 (2.8 cm / GW) and Comparative Example 2 (3.5 cm / GW). Comparative Examples 1 and 2 had uniform high concentrations of Er³⁺. + When doped (20 at%), the absorption is close to saturation at low light intensity, and the ESA effect cannot be effectively utilized. However, the gradient doped structure of this invention maintains a low ground state absorption at low light intensity, and achieves a significant enhancement of nonlinear absorption through the ESA effect at high light intensity.
[0057] (2) Optical limiting performance: The high-intensity nonlinear transmittance of Examples 1-5 ranged from 1.93% to 4.12%, with limiting ratios of 8.1 to 14.0, exhibiting excellent optical limiting characteristics. Example 4 (Er / Yb gradient co-doped) achieved a limiting ratio of 14.0, the highest among all samples, indicating that Yb³ + The gradient sensitization effect effectively enhanced Er³ + The excited-state absorption efficiency.
[0058] (3) Laser damage threshold (LIDT): The LIDT of Examples 1 to 5 was 16.8 to 21.2 J / cm², which was significantly higher than that of Comparative Example 1 (8.6 J / cm²) and Comparative Example 3 (11.3 J / cm²). The high damage threshold is attributed to the gradient doping structure reducing the initial absorption density at the incident surface, the nanocomposite sintering aid reducing grain boundary defects, and the oxygen atmosphere annealing eliminating oxygen vacancy absorption centers.
[0059] Thermal conductivity test results The thermal conductivity data of Example 1 and Comparative Example 1 at different temperatures are shown in Table 4 below: Table 4 Thermal conductivity as a function of temperature (W·m) - ¹·K - ¹)
[0060] The results show that the thermal conductivity of Example 1 is higher than that of Comparative Example 1 and Comparative Example 3 in the range of 25~300℃. The higher thermal conductivity is beneficial to the rapid dissipation of heat during laser irradiation, reducing the thermal lensing effect and thermal damage, which is one of the important reasons why Example 1 has a higher LIDT.
[0061] Based on the above test results, the advantages of the gradient doping structure of this invention compared with existing uniform doping techniques are mainly reflected in the following aspects: (1) Innovation in optical limiting mechanism: In the uniform doping scheme, Er³ + Ground-state absorption (GSA) is dominant, and at high concentrations, GSA approaches saturation, limiting the potential for ESA enhancement. This invention's gradient doping scheme uses a low concentration of Er³⁺ at the incident surface.+ (5at%), so that a portion of the incident photons are used to generate the excited state Er³. + Without causing excessive ground-state absorption; as light propagates along the doping gradient direction, the light intensity increases due to gradual absorption (nonlinear absorption superposition), while Er³ + The increasing concentration provides more ESA active sites, forming a nonlinear absorption enhancement mechanism of "GSA→ESA cascade amplification".
[0062] (2) Damage threshold improvement: The gradient doping structure reduces the initial absorption cross section of the incident surface, reduces the concentrated deposition of laser energy in the surface layer, and thus suppresses surface thermal damage; at the same time, the gradient refractive index change alleviates the interlayer thermal stress mismatch.
[0063] (3) Performance optimization: The reasonable transmittance (26~33%) under low light intensity ensures normal optical signal transmission under non-laser irradiation conditions, overcoming the problem of limited practical application of uniformly high-concentration doped "normally closed" materials.
[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various modifications or equivalent substitutions to the present invention within the scope of its essence and protection. Such modifications or equivalent substitutions should also be considered to fall within the protection scope of the present invention.
Claims
1. A transparent erbium-doped yttrium aluminum garnet ceramic, characterized in that, The transparent ceramic has a gradient-changing Er along the optical axis. 3+ Doping concentration distribution, Er 3+ The doping concentration increases continuously or stepwise from the incident surface to the exit surface in the range of 5 at% to 30 at%, and the chemical composition of the transparent ceramic is (Y 1-x Er x )3Al5O 12 Where x = 0.15~0.25, and x varies gradually from x1 to x2 along the thickness direction, and 0.05 ≤ x1 <x2≤0.30。 2. The erbium-doped yttrium aluminum garnet transparent ceramic according to claim 1, characterized in that, The transparent ceramic consists of at least three layers of different Er along its thickness direction. 3+ Sublayers with varying doping concentrations are stacked sequentially, with Er between adjacent sublayers. 3+ The doping concentration difference Δx is 2at%~10at%, the thickness of each sublayer is 0.5~5mm, and the total thickness is 2~15mm.
3. The erbium-doped yttrium aluminum garnet transparent ceramic according to claim 1, characterized in that, The transparent ceramic is also doped with Yb. 3+ As a sensitizing ion, the Yb 3+ The doping concentration is 1 at% to 8 at%.
4. The erbium-doped yttrium aluminum garnet transparent ceramic according to claim 1, characterized in that, The transparent ceramic has a grain size of 5~30μm, a relative density of ≥99.95%, a linear transmittance of ≥80% at a wavelength of 1064nm, a linear transmittance of 15%~40% at a low light intensity of 532nm, and a nonlinear transmittance of ≤5% at a high light intensity of 532nm.
5. A method for preparing an erbium-doped yttrium aluminum garnet transparent ceramic according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1, using magnesium nitrate and tetraethyl orthosilicate as precursors, MgO-SiO2 nanocomposite powder was prepared by sol-gel method, and core-shell structured nanocomposite sintering aid with a particle size of 20-80 nm was obtained by calcination at 600-800℃ for 2-4 h. S2, calcining Y2O3, α-Al2O3, Er2O3 and Yb2O3 powders at 800~1000℃ for 4~8h respectively; S3, weigh the raw material powder according to the target stoichiometric ratio of each sublayer, add core-shell structured nanocomposite sintering aid, PEG-400 dispersant and PVB binder, use anhydrous ethanol as medium and high-purity Al2O3 balls as grinding media, ball mill for 12~20h to obtain slurries of various concentration gradients. S4. After drying, grinding and sieving the slurries of each gradient, they are laid in the mold in sequence according to the designed concentration gradient. After each layer is pre-pressed, the whole is dry-pressed and then subjected to cold isostatic pressing treatment. The pressure is 200~300MPa and the holding time is 3~10min to obtain the laminated green body. S5, the green blank is subjected to air preheating, vacuum densification, high-temperature sintering and oxygen atmosphere annealing in sequence; S6, then perform hot isostatic pressing post-treatment, with a heating rate of 10~15℃ / min, and heat to 1650~1750℃ and hold for 2~4h under argon atmosphere and 150~200MPa pressure; S7, double-sided grinding and polishing to the target thickness and surface roughness.
6. The method for preparing erbium-doped yttrium aluminum garnet transparent ceramic according to claim 5, characterized in that, In step S1, the molar ratio of MgO to SiO2 is 1:1 to 3:
1.
7. The method for preparing an erbium-doped yttrium aluminum garnet transparent ceramic according to claim 5, characterized in that, In step S3, the amount of core-shell structured nanocomposite sintering aid added is 0.08~0.15wt%, the amount of PEG-400 dispersant added is 0.3~0.6wt%, the amount of PVB binder added is 0.2~0.5wt%, the solid content of anhydrous ethanol in the ball milling medium is controlled at 40~50wt%, the ball-to-material mass ratio is 2:1~4:1, and the ball milling speed is 150~250r / min.
8. The method for preparing erbium-doped yttrium aluminum garnet transparent ceramic according to claim 5, characterized in that, In step S5, the air preheating temperature is 800~1000℃, the duration is 4~8 hours, the vacuum densification temperature is 1300~1450℃, the duration is 2~4 hours, and the pressure is ≤5×10. -4 Pa, high-temperature sintering temperature is 1700~1800℃, duration is 6~12h, oxygen atmosphere annealing temperature is 1400~1500℃, duration is 8~16h, oxygen partial pressure is 0.1~1atm.
9. The method for preparing an erbium-doped yttrium aluminum garnet transparent ceramic according to claim 8, characterized in that, The heating rate during the vacuum densification stage is 2~5℃ / min, the heating rate during the high-temperature sintering stage is 1~3℃ / min, and the oxygen purity used during the oxygen atmosphere annealing stage is ≥99.999%.
10. The application of an erbium-doped yttrium aluminum garnet transparent ceramic according to any one of claims 1 to 4 in a 532nm high-power laser protection device, wherein the laser protection device comprises a laser protection lens, an optical sensor protection window, a laser processing equipment observation window, and a military optoelectronic countermeasures protection screen.